Pengaruh Inovasi Produk dan Harga terhadap Niat Beli Minuman Rasa Buah Mizone Fresin - Pradipta Rahardian (Universitas Negeri Surabaya, 2018)
Isotonic drink Mizone experienced declining sales in 2013 and the firm di product innovation to incrase sales so that on 23 April 2014 Mizone Fresin launched with a mixture different from the others with extra white tea and Vitamin B and mixed thing unique fruit suitable to accompany daily activities This study aims to analyze and discuss the influence of product innovation and price to purchase intention drink Mizone Fresin. population this research is visitors primavera futsal Surabaya who aged 18 35 years. Sample in this research were 210 respondents used multiple regression technique. Based on the results of T test known that product innovation and price have significant efect to purchase intention drink fruit flavored Mizone Fresin study in Primavera Futsal Surabaya